2000
DOI: 10.1359/jbmr.2000.15.8.1579
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Cadmium Exposure and Osteoporosis

Abstract: Osteoporosis is a major cause of morbidity worldwide. A number of risk factors, such as age and gender, are well established. High cadmium exposure causes renal damage and in severe cases also causes osteoporosis and osteomalacia. We have examined whether long-term low-level cadmium exposure increases the risk of osteoporosis. Bone mineral density (BMD) in the forearm was measured in 520 men and 544 women, aged 16 -81 years, environmentally or occupationally exposed to cadmium, using dual-energy X-ray absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
124
3
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(142 citation statements)
references
References 37 publications
13
124
3
2
Order By: Relevance
“…Data from Sweden showed a doubling of the risk for osteoporosis for urinary Cd levels of 0.5-3 lg Cd/g creatinine (middle tertile) compared with the lowest tertile (\0.5 lg Cd/g) (Alfvén et al 2000). In addition, an increased risk of fractures was also noted in the Swedish Oscar study, demonstrating an elevated hazard ratio already at exposure levels of 2-4 lg/g creatinine .…”
Section: Osteoporosismentioning
confidence: 91%
See 1 more Smart Citation
“…Data from Sweden showed a doubling of the risk for osteoporosis for urinary Cd levels of 0.5-3 lg Cd/g creatinine (middle tertile) compared with the lowest tertile (\0.5 lg Cd/g) (Alfvén et al 2000). In addition, an increased risk of fractures was also noted in the Swedish Oscar study, demonstrating an elevated hazard ratio already at exposure levels of 2-4 lg/g creatinine .…”
Section: Osteoporosismentioning
confidence: 91%
“…Clinical features associated with osteoporosis include increased morbidity (pain, physical impairment, decreased quality of life), increased risk of new fractures and increased mortality (Van der Klift et al 2002). Studies among populations from Belgium (Staessen et al 1999;Schutte et al 2008b), Sweden (Järup et al 1998a;Alfvén et al 2000;Å kesson et al 2006), Japan and China Jin et al 2004;Wang et al 2003) showed associations between osteoporosis and low-level environmental Cd exposure. The generally accepted interpretation has been that Cd-induced renal tubular damage (Staessen et al 1994) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria and decreased bone mineral density, and hence increased fracture risk (Järup et al 1998c;Staessen et al 1994) particularly in postmenopausal women (Schutte et al 2008b;Staessen et al 1999) or men in the older age group .…”
Section: Osteoporosismentioning
confidence: 99%
“…The long-term precision CV for L 2 -L 4 was less than 1% during the study period. Volumetric BMD (g/ cm 3 ) was estimated by assuming the femoral neck to be a cylinder. The average diameter at the femoral neck was obtained from Lunar software that uses a fixed length (k ¼ 1.5 cm).…”
Section: Assessment Of Bmd and Fracturesmentioning
confidence: 99%
“…We used analysis of covariance (ANCOVA) to assess the adjusted mean of BMD by three categories of U-Cd, and statistical differences were assessed using Fisher's least significant difference (LSD) test. The U-Cd categories: <0.50 (77%), 0.50 to 0.75 (17%), and !0.75 (6%) mg/g of cr were chosen to facilitate comparisons with previous studies (3,7) and because few subjects had U-Cd > 1 mg/g of cr (n ¼ 46). In logistic regression, U-Cd was included in the models either as a continuous variable rescaled to a 0.42 mg/g of cr (equivalent to 2 SD increase), allowing the coefficients to be interpreted directly in the same way as binary inputs, (24) or as categories.…”
Section: Assessment Of Bmd and Fracturesmentioning
confidence: 99%
See 1 more Smart Citation